Neurovascular Neuropsychology - Lazar, Ronald M. (Springer, 2017)
This book provides a major step in the direction of a new subspecialty, neurovascular neuropsychology. For too long the emphasis has been on seemingly compartmentalized cerebral functions which, caused by disease, have carried names like the aphasias, apraxias, agnosias, even motor-system disorders, deafness, and blindness. The purpose of this book is to present methodology and data that support the use of neuropsychological techniques as a means of shedding light on cere- bral localization, plasticity and vascular pathophysiology. The authors have demonstrated how unique insights into brain mechanisms are derived from observing the neuropsychological outcomes of systematic investigation of hemodynamics, neurotransmitter systems, blood oxygenation levels and cardiac failure. The implications of these findings bear directly on our understanding of the nature and extent of disease, disease progression, treatment efficacy, and prognosis for recovery or disease recurrence.